The Synergy of Minds and Machines: Rethinking the AI-HI Relationship through Dialectical Reconstruction - MOGAJI, Ridwan Ishola; MOTADEGBE, Adewale Oluwaseun (Àgídìgbo: ABUAD Journal of the Humanities, 2025)
Today, there is an issue regarding the superiority of intelligence regarding the nature of human intelligence and artificial intelligence. Human intelligence, which refers to the natural capacity of humans to think, reason, learn, and adapt to new situations based on experience and emotional instincts, represents the core of what it means to be human. Artificial intelligence on the other hand is the simulation of human cognitive functions by machines, especially in tasks such as problem-solving, pattern recognition, and decision-making, which often operates based on algorithms and data, both of which are unique and important in themselves. However, there is a presupposition by some commentators, which happens to be the problem of this paper. On the one hand, there is the argument that artificial intelligence; particularly generative artificial intelligence, can perform tasks better than humans, while on the other hand, is the argument that human consciousness and creativity remain irreducible, both of which have sparked renewed discussions about whether AI can rival or even surpass human cognition. However, rather than reduce the discourse to a binary conflict, this paper through a critical and dialectical method, critically engages with established perspectives, proposing a complementary view that reconciles both intelligences. It argues that artificial intelligence represents an existential evolution that targets enhancing human productivity rather than replacing humans. Contrary to fears that artificial intelligence diminishes human relevance, this paper demonstrates how it complements human intelligence by ensuring collaboration and improved productivity in advancing knowledge and innovation.